Research of Entrepreneurial Candidate: Exploring Motivation and Prospective Technological Innovation in Singapore - Sheng, Chen (American Journal of Social Sciences and Humanities, 2019)
The research looks at the relationship between the motivations and prospective technological innovation of entrepreneurial candidate in Singapore. The study seeks to discover and develop a model of the link between the motivation and innovation. A research model was developed around eight hypotheses. Two questionnaires of twenty-two items was distributed to candidates who eager to start their new business in Singapore. One hundred and twenty six valid responses were received and analyzed. The findings from this study will be useful beyond creating a better understanding and appreciation of the alignment between motivations and prospective technological innovation. Understanding the trend of behaviors from candidate to start-up entrepreneur, it would be better to explore what it will take to increase the likelihood of entrepreneurial success as ways of social and economic development. The study furnished some useful conclusions to candidate of entrepreneurship that which kinds of innovation could be utilized around the different motivation by themselves.